Dissolved Organic Carbon Source Influences Tropical Coastal Heterotrophic Bacterioplankton Response to Experimental Warming - Lønborg, Christian; Baltar, Federico; Carreira, Cátia; Morán, Xosé Anxelu G. (Frontiers in Microbiology, 2019)
Global change impacts on marine biogeochemistry will be partly mediated by heterotrophic bacteria. Besides ocean warming, future environmental changes have been suggested to affect the quantity and quality of organic matter available for bacterial growth. However, it is yet to be determined in what way warming and changing substrate conditions will impact marine heterotrophic bacteria activity. Using short-term (4 days) experiments conducted at 3 temperatures (-3°C, in situ, +3°C) we assessed the temperature dependence of bacterial cycling of marine surface water used as a control and 3 different dissolved organic carbon (DOC) substrates (glucose, seagrass and mangrove) in tropical coastal waters of the Great Barrier Reef, Australia. Our study shows that DOC source had the largest effect on the measured bacterial response, but this response was amplified by increasing temperature. We specifically demonstrate that 1) extracellular enzymatic activity and DOC consumption increased with warming, 2) this enhanced DOC consumption did not result in increased biomass production, since the increases in respiration were larger than for bacterial growth with warming, and 3) different DOC bioavailabilities affected the magnitude of the microbial community response to warming. We suggest that in coastal tropical waters, the magnitude of heterotrophic bacterial productivity and enzyme activity response to warming will depend partly on the DOC source bioavailability.